1995
DOI: 10.1177/0265407595123006
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Love

Abstract: What does it mean to love someone? In particular, does it mean the same thing across time and space, or does its meaning change with context? Is the emotional experience of love, regardless of how people define love, always the same, or does the experience of love vary with context? In this article, we argue for a social-constructionist view of love, according to which both the definition and the emotional experience of love are contextually bound. We review both the social history and the psychological backdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 63 publications
0
38
0
5
Order By: Relevance
“…It might be argued that these variances stem from the contextual nature of love (cf. Beall & Sternberg, 1995). That is, the social construction of traditional gender roles and associated ''love stories'' (cf.…”
Section: Discussionmentioning
confidence: 99%
“…It might be argued that these variances stem from the contextual nature of love (cf. Beall & Sternberg, 1995). That is, the social construction of traditional gender roles and associated ''love stories'' (cf.…”
Section: Discussionmentioning
confidence: 99%
“…However, extant research seems to be solely of U.S. origin, even though cross-cultural differences are very likely. For example, research based on interpersonal relationship theory (Beall and Sternberg, 1995;Deschamps et al, 1997) shows that culture influences the conceptualization and dimensions of the love construct.…”
mentioning
confidence: 99%
“…This is a limitation since previous research based on interpersonal relationship theory has indicated that culture influences love construct dimensionality and conceptualisation (Beall & Sternberg, 1995 concluding that consumers in France could not relate to a feeling of love towards a brand. Subsequently, they opted for an innovative survey method, in order to screen out consumer reluctance or concept unfamiliarity.…”
Section: Previous Brand Love Researchmentioning
confidence: 90%